Social Prejudice and Discriminatory Behavior Experienced in Individuals Who Have Beauty Privilege - Rasyid, Mirantih; Barkhia, Aldi; Fadhlurohman, Muhammad; Nor, As’liyanti (Budapest International Research and Critics University, 2021)
The purpose of the study was to find out how to portray individuals who have beauty privilege to social prejudice, how to portray individuals who have beauty privilege to discriminatory behavior, and to find out the factors that influence social prejudice and discriminatory behavior towards individuals who have beauty privilege. This research is qualitative research. The research used is descriptive qualitative research. Descriptive qualitative research is in the form of research with a method or approach of case study (case study). The study subjects numbered 4 women who were taken in purposive sampling. The results showed that all four subjects in the study gained social prejudice as well as experienced discriminatory behavior. The dominant factor influencing social prejudice is interlocution, in which the subject experiences the act of a conversation leading to hostility, verbally degrading attitudes, and having racial jokes (cultural and racial differences) to a particular person or group of people.